Insomnia and menopause: a narrative review on mechanisms and treatments. (1st November 2020) - Proserpio, P.; Marra, S.; Campana, C.; Agostoni, E. C.; Palagini, L.; Nobili, L.; Nappi, R. E.
Abstract: The menopausal transition is associated with an increased frequency of sleep disturbances. Insomnia represents one of the most reported symptoms by menopausal women. According to its pathogenetic model (3-P Model), different predisposing factors (i.e. a persistent condition of past insomnia and aging per se) increase the risk of insomnia during menopause. Moreover, multiple precipitating and perpetuating factors should favor its occurrence across menopause, including hormonal changes, menopausal transition stage symptoms (i.e. hot flashes, night sweats), mood disorders, poor health and pain, other sleep disorders and circadian modifications. Thus, insomnia management implies a careful evaluation of the psychological and somatic symptoms of the individual menopausal woman by a multidisciplinary team. Therapeutic strategies encompass different drugs but also behavioral interventions. Indeed, cognitive behavioral therapy represents the first-line treatment of insomnia in the general population, regardless of the presence of mood disorders and/or vasomotor symptoms (VMS). Different antidepressants seem to improve sleep disturbances. However, when VMS are present, menopausal hormone therapy should be considered in the treatment of related insomnia taking into account the risk–benefit profile. Finally, given its good tolerability, safety, and efficacy on multiple sleep and daytime parameters, prolonged-released melatonin should represent a first-line drug in women aged ≥ 55 years.